Problematika dan solusi integrasi Pendidikan Agama Islam dengan Sains di Madrasah - Darsyah, Syukron (STAIN Bengkalis, 2023)
The integration of Islamic religious education with science is an important topic in the current Islamic education system. The main focus of writing this article is about the obstacles and problems faced in implementing the integration of Islamic Religious Education with science in madrasas and the offer of integration solutions in these institutions. This article uses a type of library research. Literature review is a study of reading material that is specifically related to the object being discussed. This writing uses the literature review method. The existing literature will then be sorted and analyzed in depth and measurably. Meanwhile, the data analysis technique uses content analysis. This paper finds that the obstacles to implementing the integration of Islamic Religious Education with science in madrasas include: First, learning science and modern science is focused on the transformation of knowledge alone, Second, the teacher's educational background, Third, the curriculum is not yet integrated, Fourth, the lack of facilities and infrastructure and reading sources for religious material, especially those related to science. Fifth, the systems, approaches, strategies and methods applied in the Islamic religious education and learning process still do not fully integrate science and technology. The formulation offer for the integration of Islamic Religious Education is going well in madrasas, namely by reconstructing the curriculum, developing the creative potential of students' imagination and building a holistic and not partial conception of students' thinking.